Museum materialities : objects, engagements, interpretations - Dudley, Sandra H. (New York : Routledge, 2009)
Museum materialities : objects, sense and feeling / Sandra H. Dudley ## Photographs and history : emotion and materiality / Elizabeth Edwards ## Remembering the dead by affecting the living : the case of a miniature model of Treblinka / Andrea Witcomb ## Touching the Buddha : encounters with a charismatic object / Christopher Wingfield ## Contemporary art : an immaterial practice? / Helen Pheby ## The eyes have it : eye movements and the debatable differences between original objects and reproductions / Helen Saunderson, Alice Cruickshank and Eugene McSorley ## Experiencing materiality in the museum : artefacts re-made / Alexander Stevenson ## Virginia Woolf's glasses : material encounters in the literary/artistic house museum / Nuala Hancock ## When ethnographies enter art galleries / Lydia Nakashima Degarrod ## Engaging the material world : object knowledge and Australian journeys / Kirsten Wehner and Martha Sear ## Watch your step : embodiment and encounter at Tate Modern / Helen Rees Leahy ## Reconsidering digital surrogates : toward a viewer-orientated model of the gallery experience / Bradley L. Taylor ## Dancing pot and pregnant jar? : on ceramics, metaphors and creative labels / Wing Yan Vivian Ting ## Myth, memory and the senses in the Churchill Museum / Sheila Watson ## Dreams and wishes : the multi-sensory museum space / Viv Golding ## Making meaning beyond display / Chris Dorsett ## Authenticity and object relations in contemporary performance art / Klare Scarborough ##
Includes bibliographical references and index.
boek